Antibody to the filarial antigen Wb123 reflects reduced transmission and decreased exposure in children born following single mass drug administration (MDA). - Cathy Steel; Joseph Kubofcik; Eric A Ottesen; Thomas B Nutman (PLoS Neglected Tropical Diseases, 2012)
Background Antibody (Ab) to the Wuchereria bancrofti (Wb) infective larval (L3) antigen Wb123, using a Luciferase Immunoprecipitation System (LIPS) assay, has been shown to be a species-specific, early marker of infection developed for potential use as a surveillance tool following transmission interruption post mass drug administration. To examine its usefulness in a single filarial-endemic island assessed at two time points with markedly different levels of transmission, Ab to Wb123 was measured in sera collected from subjects from Mauke, Cook Islands in 1975 (no previous treatment) and 1992 (5 years after a one time island-wide treatment with diethylcarbamazine [DEC]). Findings Between 1975 and 1992, Wb transmission decreased dramatically as evidenced by reduced prevalences of microfilariae (31% vs. 5%) and circulating Ag (CAg, 49% vs. 16%). Age specific prevalence analysis showed a dramatic reduction in Wb123 Ab positivity from 54% (25/46) in 1975 to 8% (3/38) in 1992 in children 1-5 years (p<0.0001), reflecting the effects of single-dose treatment five years earlier. By 1992, Wb123 Ab prevalence in children 6-10 years had fallen from 75% (42/56) in 1975 to 42% (33/79) consistent with a lower cumulative transmission potential. In the whole population, Wb123 seropositivity decreased from 86% to 60% between 1975 and 1992. In CAg+ subjects the levels of Wb123 Ab were indistinguishable between the 2 time points but differed in those who were CAg- (p<0.0001). In paired sample analysis, individuals who were CAg+ in 1975 but became CAg- in 1992 had significantly lower Ab levels in 1992 (p<0.0001), with 9/40 (23%) becoming seronegative for Wb123. Conclusions The relationship between reduction in Wb123 Ab prevalence and the reduction of transmission, seen most clearly in young children, strongly advocates for the continuing assessment and rapid development of Wb123 as a surveillance tool to detect potential transmission of bancroftian filariasis in treated endemic areas.